Pelaksanaan Pemungutan Bea Perolehan Hak Atas Tanah Dan Bangunan (BPHTB) Terkait Hibah Wasiat Di Kabupaten Ponorogo - Permatasari, Bela; Sukmadewi, Yudhitiya Dyah; Supriyadi, Supriyadi (KADARKUM: Jurnal Pengabdian Kepada Masyarakat, 2024)
Building Rights Acquisition Fee (BPHTB), is a tax imposed on the acquisition of land and building rights. The object of the BPHTB tax is the acquisition of rights to land and/or buildings and the Will Grant is the object of the Land and Building Rights Acquisition Fee (BPHTB) which takes effect after the grantor of the will dies. Fees for Acquisition of Land and Building Rights for Will Grants were chosen as the topic of discussion because the implementation of the collection of BPHTB for Will Grants in Ponorogo Regency, where many taxpayers still do not know what BPHTB is, how to calculate it and how it is implemented, is what taxpayers must go through in paying BPHTB. This type of research is sociological juridical, with analytical descriptive research specifications. The sampling method used in this research uses a purposive sampling method, with data collection methods through literature studies and field studies, which are then analyzed using qualitative analysis methods. The results of the research show that in the implementation of the collection of Land and Building Rights Acquisition Fees there are several obstacles, including minimum taxpayer knowledge regarding Land and Building Rights Acquisition Fees (BPHTB). Meanwhile, to resolve these obstacles, BPPKAD carries out outreach. Taxpayers' ignorance in calculating the Land and Building Rights Acquisition Fee (BPHTB) is a problem for this problem. BPPKAD has a solution in the form of assistance in the calculation process. There are several stages in the collection process, namely the first stage when the tax is payable, the second stage calculating the amount of Land and Building Rights Acquisition Fee that must be paid and the third stage payment.